Planning control over rural land transformation in Hong Kong: A remote sensing analysis of spatio-temporal land use change patterns. (August 2022) - LIANG, Jingmin; CHEN, Jiayu; TONG, De; LI, Xin
Abstract: Urbanization has led to the expansive conversion of farmland to non-agricultural human settlements. Over the past decades, the rural New Territories in Hong Kong have experienced significant land use changes where agricultural land has become sites for industrial operations (known as brownfields in Hong Kong). This includes open storage for industrial recyclables and warehouses for repairs, many being unauthorized development. The existence of these industrial activities initially driven by socio-economic factors has persisted, largely due to absent or loose land use regulations. The Hong Kong government thus has successively incorporated increasingly more rural areas into the city's zoning ordinance system, but seemingly has generated marginal impact on reducing non-conforming land uses. How has rural land use transformed in response to planning controls like zoning? How have the spatial patterns of different types of brownfields changed over periods with varying land use regulation focuses? Focusing on rural areas in Hong Kong, this study aimed to examine the temporal and spatial patterns of different operational types of brownfields based on refined land use classification results generated by a support vector machines tool with remote sensing data from 2000 to 2020. Furthermore, this study analyzed the impact of zoning regulations on land use activities in terms of the transition flow, spatial concentration level, morphological characteristics, and transition probability of various land use types. The results show that, despite regulatory control over rural land and strengthened enforcement measures, brownfields continue to grow in a decentralized and fragmented fashion. Our findings suggest that exercising police power through zoning has its limitations on curbing unauthorized development; additionally, the Hong Kong government may supplement enforcement measures with alternative planning tools such as land swaps and incentive zoning. Highlights: Brownfields in Hong Kong mostly appeared in the New Territories. Brownfield distribution became decentralized and fragmented from 2000 to 2020 in Hong Kong. Support Vector Machine can be used to process remote sensing images. Rural land transformation pattern is affected by outline zoning plan.